Qualidade de sementes de soja tratadas com pó de diásporos de Magonia pubescens A.St.-Hil - Silva, Ana Mayra Pereira da (2019)
The objective of this work was to evaluate the physiological and sanitary quality of soybean seeds (Glicyne max) treated with timbó seeds coat (Magonia pubescens A.St.-Hil) and the fungistatic or fungitoxic potential of the timbó seed coat in vitro. The timbó seeds were collected from ripe fruits in the Cerrado. The external layer of the seed coat was removed and crushed in a mill and used in the treatment of soybean seeds and in vitro tests. For the evaluation of the physiological and sanitary quality, three seed lots were used, from seeds of high, medium and low vigor. The treatments were: powder (200 g of powder for 100 kg of seeds); Gel (2 g of powder dissolved in 100 mL of water); hidroalcoholic extract (300 ML of extract for 100 kg of seeds); synthetic fungicide (carboxin + thiram) and untreated seeds. The physiological quality of soybean seeds was determined by the pattern test of germination, accelerated aging, emergence in sand and, length, fresh and dry mass of seedlings. To determine the sanitary quality, the "blotter test" of soybean seeds was performed. For the in vitro tests, we used the Colletotricum truncata and Phomopsis sojae fungi isolated from soybean seeds in Potato-Dextrose-Agar culture medium (BDA). The following treatments were tested in the in vitro control: with synthetic fungicide; powder (8 g L-1 of BDA Medium); hydroalcoholic extract (150 ML-1 medium BDA); dry extract (8 g L-1 of BDA Medium). In the second experiment, the powder timbó seeds coat was added in the proportion of 0, 2, 4, 6 or 8 G L-1 of the culture medium. The evaluations were made by means of measurements of the diameter of the colonies and the percentage of inhibition of mycelial growth (PIC) was determined. The statistical design used for seed quality was completely randomized in a 3x5 factorial scheme, considering three seed lots and five treatments. The in vitro tests were completely randomized, with five treatments and ten replications. The treatment with the extract and gel of the timbó seed coat improves the physiological quality of soybean seeds from low vigor lots. The treatment of seeds with gel of the timbó seeds decreases the incidence of Fusarium spp. and Penicillium genus; and the treatment with the powder reduced the incidence of the Cercospora sp genus. The powder, the hydroalcoholic and dry extract of the timbó seeds coat present fungistatic activity on the mycelial growth of Colletotricum trunchatum and Phomopsis sojae, except the powder for Phomopsis sojae and the maximum inhibition of mycelial growth for Colletotricum trunchatum and Phomopsis Sojae is 8 g L-1 of powder of timbó seeds coat.